Molecular features of neural stem cells enable their enrichment using pharmacological inhibitors of survival‐promoting kinases. (10th October 2013) - Brazel, Christine Y.; Alaythan, Abdulaziz A.; Felling, Ryan J.; Calderon, Frances; Levison, Steven W.
Abstract Isolating a pure population of neural stem cells (NSCs) has been difficult since no exclusive surface markers have been identified for panning or FACS purification. Moreover, additional refinements for maintaining NSCs in culture are required, since NSCs generate a variety of neural precursors (NPs) as they proliferate. Here, we demonstrate that post‐natal rat NPs express low levels of pro‐apoptotic molecules and resist phosphatidylinositol 3′OH kinase and extracellular regulated kinase 1/2 inhibition as compared to late oligodendrocyte progenitors. Furthermore, maintaining subventricular zone precursors in LY294002 and PD98059, inhibitors of PI3K and ERK1/2 signaling, eliminated lineage‐restricted precursors as revealed by enrichment for Nestin+/SOX‐2+ cells. The cells that survived formed neurospheres and 89% of these neurospheres were tripotential, generating neurons, astrocytes, and oligodendrocytes. Without this enrichment step, less than 50% of the NPs were Nestin+/SOX‐2+ and 42% of the neurospheres were tripotential. In addition, neurospheres enriched using this procedure produced 3‐times more secondary neurospheres, supporting the conclusion that this procedure enriches for NSCs. A number of genes that enhance survival were more highly expressed in neurospheres compared to late oligodendrocyte progenitors. Altogether, these studies demonstrate that primitive neural precursors can be enriched using a relatively simple and inexpensive means that will facilitate cell replacement strategies using stem cells as well as other studies whose goal is to reveal the fundamental properties of primitive neural precursors. <boxed-text content-type="graphic" id="jnc12447-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Neural stem cells resist death effectors, which contributes to their longevity. We demonstrate that primitive Subventricular Zone neural precursors express low levels of pro‐apoptotic molecules and resist PI3K (PD98059) and ERK1/2 (LY‐294002) inhibition. By contrast, progenitors expressed higher levels of cell‐death signaling molecules. Using combinations of PI3K and ERK1/2 inhibitors, cultures highly enriched in tripotential neural precursors were produced.